(NmINERALOOBRAZOWANIE W GIDROTERMALXNYH SISTEMAH (B:s ((NfIZI^ESKIE I FIZIKO(B-(NHIMI^ESKIE USLOWIQ(B) /s - (NpAMPURA(B, (NwIKTOR dMITRIEWI^s; (NlETNIKOW(B, (Nf(B. (Na(B.s; (NiN(B-(NT GEOHIMII IM(B. (Na(B.(Np(B. (NwINOGRADOWA so an sssrs ((NmOSKWA (B:s (NnAUKA(B,s, 1977)
(NbIBLIOGR(B. 195 (NNAZ(B.s
Keywords: (NgEOLOGIQs